The Influence of Brand Image, Perception of Ease and Perception of Risk on Purchase Intention through Trust in Shopee - Dian Citaningtyas Ari Kadi; Meydina Surya Amalia (Cita Konsultindo Research Center, 2021)
.This research is entitled